Analysis of Factors Influencing Livestock Farmers' Responses To Artificial Insemination Technology In Bontocini Village, District Rumbia , Jeneponto Regency - Hartina Beddu; Muhammad Yunus; Irma Irma; Kartika Ekasari Z; Alfian Fadhil Jalal (Jurnal Agrisistem: Seri Sosek dan Penyuluhan, 2026)
Insemination technology is one of the efforts to increase the productivity and genetic quality of livestock, but the level of response of farmers to this technology is still varied. This study aims to analyze the factors that influence the response of farmers to Insemination technology in Bontocini Village, Rumbia District, Jeneponto Regency. The study was conducted from May to July 2024 in Bontocini Village, Rumbia District, Jeneponto Regency. The study method used a survey with data collection through questionnaires given to cattle farmers in Bontocini Village, Rumbia District, Jeneponto Regency. The results showed that simultaneously the factors forming perceptions significantly influenced the response of farmers to Insemination technology. Partially, farmer knowledge (X1) had no significant effect, while the attitude of farmers (X2) with a significance value of 0.009 and ease of access to Insemination services (X3) with a significance value of 0.000 significantly influenced the response of farmers. The regression equation obtained is Y = -0.190 + 0.655X2 + 0.644X3, which shows that the response of farmers increases along with more positive attitudes and easier access to Insemination services.